Pengaruh Edukasi Gizi Melalui Media Booklet terhadap Perubahan Pilihan Makanan Camilan pada Remaja di Makassar - Andi Sri Rahayu Kasma (Nutrition Science and Health Research, 2022)
Snacking activity has been identified as one of the potential causes of obesity and/or overweight in childhood and adolescence. According to Hampl, a child is snacking more than 15-20% of his daily calorie intake of snacks can be defined as "snacker". Snack is thought to be the promoter of obesity because it contains high fat and high sugar. This study is a quantitative research design with quasy experiment. This study was done to see if there are changes in the selection of snacks to students at Senior High School 16 Makassar before and after nutrition education through the booklet media. The population of this research is the students of class X and XI Senior High School 16 Makassar, with a total sample of 59 students. The sample was conducted using stratified random sampling. The results showed that there are change choice healthy snack (p=0,011) and sweet snack (p=0,046) before and after the intervention. There are also changes in the number of healthy snacks consumption (p=0,02) and sweet snack (p=0,041). The conclusion from this study that there is change choice snack before and after nutrition education through the booklet media at Senior High School 16 Makassar.